Comparison between phenotypic and PCR for detection of OXA-23 type and metallo-beta-lactamases producer Acinetobacter spp. - Azimi, Leila; Lari, Abdolaziz Rastegar; Talebi, Malihe; Namvar, Amirmorteza Ebrahimzadeh; Jabbari, Mosadegh (German Medical Science GMS Publishing House, 2013)
[english] Background: Resistance to carbapenems is developing around the world and can cause many problems for treatment of patients. Production of metallo-beta-lactamase (MBL) is one of the main mechanism for this type of resistance. So, detection of MBL-producer microorganisms can prevent the spread of this type of resistance.Materials and methods: In this study 94 spp. were investigated. Resistance to imipenem was conducted after purification and identification. Combination disc (CD) and Double Disc Synergy Test (DDST) were performed for phenotypic detection of MBL and the molecular PCR method was done for vim-1, vim-2, imp-1 and OXA-23 genes.Results: According to TSI, SIM and oxidation-fermentation (OF) test and PCR assay 93 and one strain were identified. 85% of them were resistant to imipenem. 34% of them have a positive combination disc test (CD) while Double Disc Synergy Test (DDST) was negative for all of them. The vim-1, vim-2 and imp-1 genes were not detected in PCR molecular method, however in 74% of strains with positive results in combination disc, were positive for the OXA-23 gene after PCR test. This study shows that the blaOXA-23 resistance determinant may become an emerging therapeutic problem.Discussion: According to the results, it seems that combination disc does not have enough specificity for detection of MBL-producer and using Double Disc Synergy Test (DDST) can be more convenient.